The Culture Construction of Eid Ghadir Commemorations In Indonesia - Masrukhin, Agus; Dienaputra, Reiza D; Suganda, Dadang; Nurhayati Ma’mun, Titin (Opción, 2019)
The purpose of this research is to analyze the culture construction of Eid of Ghadir Commemoration in Indonesia especially in Jakarta and Bandung, revealing the cultural factors behind the tradition of Eid of Ghadir comme- morations in Jakarta and Bandung. This research uses cultural research methods in descriptive qualitative form with stages covering two appro- aches, namely: Intrinsic Approach and Extrinsic Approach. The results of the research revealed that the commemoration of Eid of Ghadir has a great significance for Syiah groups, including through the approach of Peter L Berger's construction theory approach and analysis through the construction of Koentjaraningrat cultural construction, that the Eid of Ghadir commemoration is a great culture of the Syiah group with elements of theif, sociafacts and artifacts.